INSULIN-LIKE GROWTH FACTORS AND INSULIN-LIKE GROWTH FACTOR BINDING PROTEINS AND PROSTATE CANCER RISK: RESULTS FROM THE PROSTATE CANCER PREVENTION TRIAL - Neuhouser, Marian L (2013)
The role of the insulin-like growth factor (IGF) axis and whether IGFs interact with androgen-suppressing agents in relation to prostate carcinogenesis is unclear. This nested case-control study (n=1652 cases/1543 controls) examined whether serum IGF1, IGF2, IGFBP2, IGFBP3 and the IGF1:IGFBP3 ratio were associated with prostate cancer in the Prostate Cancer Prevention Trial, a randomized, placebo-controlled trial of finasteride for prostate cancer prevention. Presence or absence of cancer was determined by prostate biopsy. Baseline serum was assayed for IGF-axis analytes using ELISA. Logistic regression estimated odds ratios and 95% confidence intervals for risk of total, low-grade (Gleason 2–6) and high-grade (Gleason 7–10) cancers. Results were stratified by intervention assignment. In both the placebo and finasteride arms, serum IGF1, IGF2, IGFBP3 and the IGF1:IGFBP3 ratio were not associated with prostate cancer. However men in the highest vs. lowest quartile of serum IGFBP2 had a 48% (P-trend =0.02) and 55% (P-trend=0.01) increased risk for total and low-grade cancers respectively. These IGFBP2 associations were attenuated and no longer statistically significant in the finasteride arm. Our results suggest that in general, serum IGF-axis analytes were not associated with prostate cancer risk in the PCPT where presence or absence of all cancers was biopsy-determined. The exception was the finding that high serum IGFBP2 is a risk factor for low-grade disease, which was attenuated for men on finasteride. Further research is needed to understand better the risk incurred by high IGFBP2 and whether androgen-suppressing agents such as finasteride influence aspects of IGFBP2 physiology relevant to prostate carcinogenesis.